Redox flow batteries — perspective means of electrochemical energy storage - Sakhnenko, Mykola; Ved, Maryna; Bairachna, Tetiana; Shepelenko, Oleksandr; Ziubanova, Svitlana (Technology audit and production reserves, 2013)
The article comprises the overview of redox flow battery (RFB) technology. The RFBs are best known as perspective means of electrochemical energy storage to supplement such renewable but unfortunately intermittent and poorly predictable sources of energy as wind and/or solar energy. The description of RFB concept as well as its application, advantages and shortcomings in comparison with traditional lithium-based batteries are provided. The current state of research on RFBs is discussed. The list of redox couples and electrode materials used in RFBs and their performance characteristics are presented. The prospects for RFB improvement and further development are suggested and as a result the direction of scientific experiments is outlined.